Anodic oxidation liquid, anodizing method and oxidation plate

By anodizing the magnesium-aluminum composite sheet with anodized solution containing alkali, alkaline salt, molybdate or tungstate, complexing agent, and buffering agent, the problem of poor oxide film performance in the prior art is solved, and high-performance oxide film formation is achieved.

CN117661068BActive Publication Date: 2025-03-11BYD CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211028411.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-25
Publication Date
2025-03-11
Estimated Expiration
2042-08-25

AI Technical Summary

Technical Problem

The anodized film obtained by the oxidation liquid used for anodizing magnesium-aluminum composite sheets in the prior art has defects in appearance, salt spray resistance, adhesion resistance and boiling resistance.

Method used

An anodizing liquid including alkali, alkaline salt, molybdate or tungstate, complexing agent, buffering agent and water is provided, through which the metal sheet is anodized to form a uniform, complete oxide film with a high film thickness.

Benefits of technology

A uniform, complete oxide film with high film thickness is achieved on the surface of magnesium-aluminum composite sheet, which significantly improves the salt spray resistance, adhesion resistance and boiling resistance of the oxide film, while avoiding magnesium corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117661068B_ABST
    Figure CN117661068B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of anodizing technology, and discloses an anodizing liquid, an anodizing method and an oxidized plate. The anodizing liquid comprises the following components: an alkali, an alkaline salt, a molybdate and / or a tungstate, a complexing agent, a buffer and water. An oxidized plate is obtained by contacting a metal plate with the anodizing liquid for anodizing. The present invention can make the oxide film on the surface of the metal plate grow uniformly and stably through the mutual coordination of the components in the anodizing liquid, thereby forming a uniform, complete and thick oxide film on the surface of the plate, thereby achieving the purpose of surface decoration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anodizing, and in particular to an anodizing liquid, an anodizing method and an oxidation plate. Background Art

[0002] With the advent of the 5G era, the electronics industry is booming, and 3C products are gradually moving towards a lighter and thinner direction. Lightweight electronic products can not only attract consumers' attention, but also be easy for people to carry. Most of the metal structural parts used in electronic products are made of aluminum alloy. If aluminum alloy is replaced with magnesium-aluminum composite sheet, it will greatly help the thinness of electronic products. For example, changing the material of the mobile phone middle frame from aluminum alloy to magnesium-aluminum composite sheet can reduce the weight by about 20%.

[0003] Currently, metal structural parts of electronic products are usually anodized in conventional acidic solutions, but magnesium-aluminum composite panels will corrode in acidic oxidation tank liquid, seriously affecting performance and appearance.

[0004] CN110629267A discloses an alkaline anodizing liquid for aluminum products, which comprises: an alkaline salt, a buffer, an alcohol and water; the alkaline salt is a carbonate and / or a bicarbonate; the alcohol is a water-soluble alcohol, and the boiling point of the alcohol is above 60°C; the pH value of the alkaline anodizing liquid for aluminum products is 8-12.

[0005] CN1997777A discloses a method and composition for anodizing metal surfaces, and specifically relates to a method for treating a metal workpiece with an anodizing solution, a composition of the anodizing solution, and a coating prepared with the anodizing solution for anodizing metal surfaces, especially magnesium, magnesium alloys, aluminum and aluminum alloy surfaces. The composition is an alkaline aqueous solution containing a water-soluble inorganic hydroxide, an anion containing phosphorus and oxygen, at least one surfactant, and an alkaline buffer solution based on at least one alkaline hydrolyzed silane, at least one alcohol showing at least one basic group, or a mixture thereof.

[0006] CN103320840A discloses a titanium alloy anodized alkaline electrolyte and a color film preparation process. The anodized electrolyte is composed of sodium oxalate, sodium silicate, sodium dihydrogen phosphate, sodium hydroxide, and deionized water; the titanium alloy anodized color film preparation process includes bright treatment-alkali solution degreasing-water washing-constant pressure anodizing-water sealing-blow drying and other steps; it is characterized in that a pulse constant pressure control method is adopted, and the balance effect of the dissolution and growth of the TiO2 film layer in the alkaline electrolyte is used to obtain different thicknesses and roughnesses, and oxidation is carried out at a voltage of 10-120V for 10-60 minutes to obtain a bright and uniform anodized film.

[0007] There are few oxidizing solutions for anodizing magnesium-aluminum composite plates in the prior art. When the existing anodizing solutions for magnesium, magnesium alloys, aluminum, aluminum alloys, titanium, and titanium alloys are used on magnesium-aluminum composite plates, the obtained anodized films have defects in appearance, salt spray resistance, adhesion, and water boiling resistance. Summary of the invention

[0008] The purpose of the present invention is to overcome the problems of poor appearance, salt spray resistance, adhesion and water boiling resistance of the anodic oxide film obtained by using the anodic oxide liquid in the prior art for magnesium-aluminum composite plates, and to provide an anodic oxide liquid, an anodic oxide method and an oxidized plate. The anodic oxide liquid of the present invention is used for anodizing the plate, and a uniform, complete and thick oxide film can be formed on the surface of the plate, which can obtain a better surface decoration effect, and the formed oxide film exhibits excellent salt spray resistance, adhesion and water boiling resistance.

[0009] In order to achieve the above object, the first aspect of the present invention provides an anodizing solution, which comprises the following components: alkali, alkaline salt, molybdate and / or tungstate, complexing agent, buffer and water.

[0010] A second aspect of the present invention provides an anodizing method, wherein a metal plate is brought into contact with the anodizing liquid to perform anodizing.

[0011] A third aspect of the present invention provides an oxidized plate obtained by the aforementioned anodizing method.

[0012] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:

[0013] (1) The present invention can make the oxide film on the surface of the metal plate grow uniformly and stably through the mutual cooperation of the various components in the anodizing liquid, thereby forming a uniform, complete, and thick oxide film on the surface of the plate, thereby achieving the purpose of surface decoration. In practical applications, different anodizing conditions can be selected according to actual needs to obtain oxide film layers of different film thicknesses, thereby preparing plates with anodized film layers of different thicknesses.

[0014] (2) The present invention can significantly improve the salt spray resistance, adhesion and water boiling resistance of the oxide film formed on the surface of the metal plate.

[0015] (3) When the anodizing liquid of the present invention is used for anodizing of a magnesium-aluminum composite plate, it can ensure that an oxide film grows on the aluminum and prevent the magnesium from being corroded.

[0016] (4) The present invention is not only applicable to magnesium-aluminum composite plates, but can also be directly applied to magnesium alloys and aluminum alloys. At the same time, the existing anodizing production line can be directly used, which has low energy consumption and is conducive to large-scale promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a SEM image of the aluminum surface of the sample prepared in Example 3 (magnification is 50000 times);

[0018] Figure 2 This is a SEM image of the magnesium surface of the sample prepared in Example 3 (magnification is 50,000 times). DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] A first aspect of the present invention provides an anodic oxidation solution, which comprises the following components: an alkali, an alkaline salt, a molybdate and / or a tungstate, a complexing agent, a buffer and water.

[0021] In the anodizing solution of the present invention, molybdate and / or tungstate and the complexing agent have a synergistic effect, which is beneficial to the thickening of the film layer and the improvement of the uniformity of film formation, and can ensure that both sides of the plate grow uniformly and stably in the oxidation solution, thereby forming a complete and uniform anodized film layer. The buffering agent can adjust the pH value of the anodizing solution, thereby ensuring that the plate can undergo an anodizing reaction uniformly and stably in the anodizing solution.

[0022] The present invention can make the oxide film on the surface of the metal plate grow evenly and stably through the mutual coordination of alkali, alkaline salt, molybdate and / or tungstate, complexing agent and buffer, so as to form a uniform, complete and thick oxide film on the surface of the plate, thereby achieving the purpose of surface decoration, and the formed oxide film can show excellent salt spray resistance, adhesion performance and water boiling resistance.

[0023] The anodizing liquid of the present invention is obtained by uniformly mixing the above components.

[0024] In some embodiments of the present invention, the pH value of the anodizing solution is greater than 7, such as 8, 9, 10, 11, 12, 13, 14, and any value in the range of any two of the above values, preferably 10-13. In other words, the anodizing solution of the present invention is an alkaline anodizing solution, which can avoid corrosion of magnesium. The preferred pH value range of 10-13 can ensure that the magnesium-aluminum composite plate grows an oxide film uniformly and stably.

[0025] In some preferred embodiments of the present invention, the cations of the molybdate and / or tungstate are the same as those of the complexing agent. For example, the cations of the molybdate and / or tungstate and the complexing agent are both sodium ions, that is, the anodic oxidation solution includes sodium molybdate and / or sodium tungstate, and sodium tartrate. In the present invention, the molybdate and / or tungstate and the complexing agent having the same cations are selected to ensure that the oxidation reaction proceeds more smoothly.

[0026] In some preferred embodiments of the present invention, the mass ratio of the molybdate and / or tungstate to the complexing agent is 1:0.25-4, such as 1:0.25, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, and any value in the range of any two of the above values, preferably 1:1. If the above mass ratio is too large, the uniformity of film formation will deteriorate; if the above mass ratio is too small, it is not conducive to the thickening of the film layer.

[0027] In some embodiments of the present invention, the base is a hydroxide and / or ammonia. In some preferred embodiments of the present invention, the hydroxide is sodium hydroxide and / or potassium hydroxide. Typical but non-limiting examples include: sodium hydroxide, potassium hydroxide, ammonia, a combination of sodium hydroxide and potassium hydroxide, a combination of sodium hydroxide and ammonia, a combination of potassium hydroxide and ammonia, a combination of sodium hydroxide, potassium hydroxide and ammonia, etc. The preferred type of base can be used to increase the pH value of the oxidizing solution to a suitable pH range.

[0028] In some preferred embodiments of the present invention, the content of the alkali is 0.1-3g / L, for example 0.1g / L, 0.2g / L, 0.3g / L, 0.4g / L, 0.5g / L, 0.6g / L, 0.7g / L, 0.8g / L, 0.9g / L, 1g / L, 1.1g / L, 1.2g / L, 1.3g / L, 1.4g / L, 1.5g / L, 1.6g / L, 1.7g / L, 1.8g / L, 1.9g / L, 2g / L, 2.1g / L, 2.2g / L, 2.3g / L, 2.4g / L, 2.5g / L, 2.6g / L, 2.7g / L, 2.8g / L, 2.9g / L, 3g / L, and any value in the range composed of any two of the above values, preferably 0.2-2g / L. The content of the alkali in the present invention is obtained through optimization. If the content of the alkali is too low, the pH value cannot be increased to a suitable pH value; if the content of the alkali is too high, the pH value will exceed the suitable range.

[0029] In some embodiments of the present invention, the alkaline salt is a carbonate and / or a bicarbonate. In some preferred embodiments of the present invention, the alkaline salt is selected from at least one of sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate, potassium bicarbonate and ammonium bicarbonate, preferably sodium carbonate and / or potassium carbonate. Typical but non-limiting examples include: sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate, potassium bicarbonate, ammonium bicarbonate, a combination of sodium carbonate and potassium carbonate, a combination of ammonium carbonate and sodium bicarbonate, a combination of sodium bicarbonate and potassium bicarbonate, a combination of ammonium bicarbonate and potassium bicarbonate, a combination of sodium carbonate and sodium bicarbonate, a combination of sodium carbonate, potassium carbonate and ammonium bicarbonate, a combination of potassium carbonate, ammonium carbonate and potassium bicarbonate, a combination of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate, a combination of potassium carbonate, ammonium carbonate, potassium bicarbonate and ammonium bicarbonate, a combination of sodium carbonate, potassium carbonate, ammonium carbonate, potassium bicarbonate and ammonium bicarbonate, and the like. The preferred alkaline salt of the present invention can ensure that the reaction rate of the plate in an alkaline environment is moderate and will not cause severe corrosion of the plate in the anodizing solution.

[0030] In some preferred embodiments of the present invention, the content of the alkaline salt is 20-150 g / L, for example 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L, 100 g / L, 105 g / L, 110 g / L, 115 g / L, 120 g / L, 125 g / L, 130 g / L, 135 g / L, 140 g / L, 145 g / L, 150 g / L, and any value in the range composed of any two of the above values, preferably 30-120 g / L. The content of the alkaline salt in the present invention is obtained through optimization. If the content of the alkaline salt is too low, the oxide film will be extremely thin or difficult to form; if the content of the alkaline salt is too high, the film thickness will not change or even decrease.

[0031] In some embodiments of the present invention, the molybdate is selected from at least one of sodium molybdate, magnesium molybdate, ammonium molybdate and lithium molybdate. Typical but non-limiting examples include: sodium molybdate, magnesium molybdate, ammonium molybdate, lithium molybdate, a combination of sodium molybdate and magnesium molybdate, a combination of ammonium molybdate and lithium molybdate, a combination of sodium molybdate and ammonium molybdate, a combination of potassium molybdate and lithium molybdate, a combination of sodium molybdate, magnesium molybdate and ammonium molybdate, a combination of sodium molybdate, magnesium molybdate and lithium molybdate, a combination of magnesium molybdate, ammonium molybdate and lithium molybdate, a combination of sodium molybdate, magnesium molybdate, ammonium molybdate and lithium molybdate, and the like.

[0032] In some preferred embodiments of the present invention, the tungstate is selected from at least one of sodium tungstate, magnesium tungstate, ammonium tungstate and lithium tungstate. Typical but non-limiting examples include: sodium tungstate, magnesium tungstate, ammonium tungstate, lithium tungstate, a combination of sodium tungstate and magnesium tungstate, a combination of ammonium tungstate and lithium tungstate, a combination of sodium tungstate, magnesium tungstate and ammonium tungstate, a combination of magnesium tungstate, ammonium tungstate and lithium tungstate, a combination of sodium tungstate, ammonium tungstate and lithium tungstate, a combination of sodium tungstate, magnesium tungstate and lithium tungstate, a combination of sodium tungstate, ammonium tungstate and lithium tungstate, a combination of sodium tungstate, magnesium tungstate and lithium tungstate, a combination of sodium tungstate, magnesium tungstate, ammonium tungstate and lithium tungstate, and the like.

[0033] The preferred molybdate and tungstate of the present invention can be well dissolved in the anodic oxidation solution, and are conducive to the thickening of the film layer and the improvement of the uniformity of film formation, so as to obtain a complete and uniform anodic oxidation film layer.

[0034] In some preferred embodiments of the present invention, the content of molybdate and / or tungstate is 3-30 g / L, such as 3 g / L, 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, and any value in the range of any two of the above values, preferably 5-20 g / L. The content of molybdate and / or tungstate in the present invention is obtained through optimization. If the content of molybdate and / or tungstate is too low, the film thickness will be reduced; if the content of molybdate and / or tungstate is too high, the film thickness will not change significantly or even decrease.

[0035] In some embodiments of the present invention, the complexing agent is selected from at least one of sodium oxalate, sodium citrate, disodium edetate, sodium tartrate, sodium potassium tartrate and sodium gluconate, preferably selected from at least one of disodium edetate, sodium tartrate and sodium potassium tartrate. Typical but non-limiting examples include: sodium oxalate, sodium citrate, disodium edetate, sodium tartrate, potassium sodium tartrate, sodium gluconate, a combination of sodium oxalate and sodium citrate, a combination of disodium edetate and sodium tartrate, a combination of potassium sodium tartrate and sodium gluconate, a combination of sodium oxalate, sodium citrate and disodium edetate, a combination of sodium tartrate, potassium sodium tartrate and sodium gluconate, a combination of sodium oxalate, sodium citrate, potassium sodium tartrate and sodium gluconate, a combination of disodium edetate, sodium tartrate, potassium sodium tartrate and sodium gluconate, a combination of sodium oxalate, sodium citrate, sodium tartrate, potassium sodium tartrate and sodium gluconate, a combination of sodium oxalate, sodium citrate, disodium edetate, sodium tartrate, potassium sodium tartrate and sodium gluconate, a combination of sodium oxalate, sodium citrate, disodium edetate, sodium tartrate, potassium sodium tartrate and sodium gluconate, etc. The preferred complexing agent of the present invention can be well dissolved in the anodizing solution, and is conducive to improving the uniformity of film formation, and obtaining a complete and uniform anodized film layer.

[0036] In some preferred embodiments of the present invention, the content of the complexing agent is 3-30 g / L, such as 3 g / L, 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, and any value in the range of any two of the above values, preferably 5-20 g / L. The content of the complexing agent in the present invention is obtained through optimization, and too low or too high a content of the complexing agent will reduce the uniformity of the film layer.

[0037] In some embodiments of the present invention, the buffer is selected from at least one of sodium borate, sodium acetate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate and triethanolamine, preferably sodium phosphate and / or triethanolamine. Typical but non-limiting examples include: sodium borate, sodium acetate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, triethanolamine, a combination of sodium borate and sodium acetate, a combination of sodium phosphate and sodium dihydrogen phosphate, a combination of disodium hydrogen phosphate and triethanolamine, a combination of sodium borate, sodium acetate and sodium phosphate, a combination of sodium dihydrogen phosphate, disodium hydrogen phosphate and triethanolamine, a combination of sodium borate, sodium acetate, sodium phosphate and sodium dihydrogen phosphate, a combination of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate and triethanolamine, a combination of sodium borate, sodium acetate, sodium phosphate, sodium dihydrogen phosphate and triethanolamine, a combination of sodium borate, sodium acetate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate and triethanolamine, and the like. The preferred buffer of the present invention can better adjust the pH value of the anodizing solution, thereby ensuring that the plate can be evenly and stably anodized in the anodizing solution.

[0038] In some preferred embodiments of the present invention, the content of the buffer is 3-30 g / L, such as 3 g / L, 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, and any value in the range of any two of the above values, preferably 5-20 g / L. The content of the buffer in the present invention is obtained through optimization. If the content of the buffer is too low, the pH value of the oxidizing solution cannot be effectively adjusted; if the content of the buffer is too high, the reaction rate will be reduced.

[0039] A second aspect of the present invention provides an anodizing method, wherein a metal plate is brought into contact with the anodizing liquid to perform anodizing.

[0040] In the specific operation, the anodizing liquid of the present invention is first prepared according to a specific formula, and then the metal sheet to be treated is put into the prepared anodizing liquid, anodized at a certain temperature and voltage, and taken out after a certain period of treatment to obtain a metal sheet covered with an anodized film.

[0041] The present invention can control the thickness of the oxide film layer by controlling the conditions of anodizing, that is, by adjusting the temperature, voltage and time of anodizing, so as to prepare plates with anodized film layers of different thicknesses.

[0042] In some embodiments of the present invention, the anodization method is selected from one of direct current anodization, alternating current anodization and pulse anodization, wherein the more preferred method is direct current anodization, which can ensure a stable reaction rate.

[0043] In some preferred embodiments of the present invention, the anodizing voltage is 10-100V, for example 10V, 20V, 30V, 40V, 50V, 60V, 70V, 80V, 90V, 100V, and any value in the range consisting of any two of the above numerical values; the anodizing temperature is 15-60°C, for example 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, and any value in the range consisting of any two of the above numerical values; the anodizing time is 10-120min, for example 10min, 20min, 40min, 60min, 80min, 100min, 120min, and any value in the range consisting of any two of the above numerical values. In the present invention, the above-mentioned anodizing conditions are obtained after optimization, wherein, if the anodizing voltage is too low, the film layer will be extremely thin or difficult to form, and if the anodizing voltage is too high, it will easily cause the film layer to be powdered; if the anodizing temperature is too low, the film layer will be extremely thin or difficult to form, and if the anodizing temperature is too high, it will easily cause the film layer to be powdered; if the anodizing time is too short, the film thickness will be small, and if the anodizing time is too long, there will be no obvious change in the film thickness and even cause the film layer to be powdered.

[0044] In some preferred embodiments of the present invention, the anodization voltage is 20-40 V, the anodization temperature is 20-40° C., and the anodization time is 20-60 min.

[0045] Those skilled in the art can arbitrarily select or combine the above-mentioned anodizing parameters within the above-mentioned range as long as the desired effect of the present invention can be achieved.

[0046] In some embodiments of the present invention, the method further comprises: performing a pre-treatment on the metal sheet before the anodizing.

[0047] In some preferred embodiments of the present invention, the pre-treatment includes grinding, polishing and degreasing, wherein each step also includes water washing. Those skilled in the art can select the pre-treatment method according to actual needs. The purpose of the pre-treatment is to obtain a smooth and flat surface.

[0048] For example, use 180#, 600#, 1200#, 2500#, and 4000# sandpaper for step-by-step polishing; use silica polishing liquid with a particle size of 0.05μm for polishing; use a degreasing liquid with the following composition: 5-10g / L Na2CO3, 5-10g / L Na3PO4, 3-5mL / L surfactant, and perform degreasing treatment at 30-50℃.

[0049] In some preferred embodiments of the present invention, the method further comprises: sealing the treated sheet obtained by the anodization. Since the oxide film formed by the anodization is porous and has strong chemical activity, a sealing surface treatment is required after the anodization treatment is completed. The sealing treatment can improve the hardness, wear resistance and corrosion resistance of the metal sheet surface.

[0050] In some preferred embodiments of the present invention, the sealing process includes: placing the treated plate in a nickel acetate solution for sealing for 20-60 minutes, and then drying it at 60-80°C for 10-30 minutes. The sealing time can be selected from 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, and any value in the range of any two of the above values. The drying temperature can be selected from 60°C, 65°C, 70°C, 75°C, 80°C, and any value in the range of any two of the above values. The drying time can be selected from 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, and any value in the range of any two of the above values. Those skilled in the art can arbitrarily select or combine the above parameters within the range as long as a better sealing effect can be achieved.

[0051] A third aspect of the present invention provides an oxidized plate obtained by the aforementioned anodizing method.

[0052] In some embodiments of the present invention, the oxidation plate includes a metal plate and an anodic oxide film covering at least one side of the metal plate. In actual operation, the anodic oxide film can be formed on one side or both sides of the metal plate.

[0053] In some preferred embodiments of the present invention, the metal plate is a magnesium-aluminum composite plate.

[0054] In some preferred embodiments of the present invention, the thickness of the anodized film layer on the magnesium surface of the magnesium-aluminum composite plate is 1-8 μm. In some preferred embodiments of the present invention, the thickness of the anodized film layer on the aluminum surface of the magnesium-aluminum composite plate is 1-7 μm. The above thickness range can meet the requirements of subsequent decorative and performance tests.

[0055] The present invention can make the oxide film on the surface of the metal plate grow evenly and stably through the mutual cooperation of the components in the anodizing liquid, thereby forming an even, complete and thick oxide film on the surface of the plate, and achieving the purpose of surface decoration. In practical applications, different anodizing conditions can be selected according to actual needs to obtain oxide film layers of different film thicknesses, thereby preparing plates with anodized film layers of different thicknesses. The present invention can significantly improve the salt spray resistance, adhesion performance and boiling resistance of the oxide film formed on the surface of the metal plate.

[0056] When the anodic oxidation liquid of the present invention is used for anodic oxidation of magnesium-aluminum composite plates, it can ensure that aluminum grows an oxide film and prevent magnesium from being corroded.

[0057] In addition, the present invention is not only applicable to magnesium-aluminum composite plates, but can also be directly applied to magnesium alloys and aluminum alloys. At the same time, the existing anodizing production line can be directly used, which has low energy consumption and is conducive to large-scale promotion.

[0058] According to a particularly preferred embodiment of the present invention, an anodizing solution comprises the following components: 0.1-3 g / L of alkali, 20-150 g / L of alkaline salt, 3-30 g / L of molybdate and / or tungstate, 3-30 g / L of complexing agent, 3-30 g / L of buffer and water; the pH value of the anodizing solution is 10-13;

[0059] The molybdate and / or tungstate has the same cation as the complexing agent; the mass ratio of the molybdate and / or tungstate to the complexing agent is 1:0.25-4;

[0060] The alkali is hydroxide and / or ammonia water; the alkaline salt is selected from at least one of sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate, potassium bicarbonate and ammonium bicarbonate; the molybdate is selected from at least one of sodium molybdate, magnesium molybdate, ammonium molybdate and lithium molybdate; the tungstate is selected from at least one of sodium tungstate, magnesium tungstate, ammonium tungstate and lithium tungstate; the complexing agent is selected from at least one of sodium oxalate, sodium citrate, disodium ethylenediaminetetraacetate, sodium tartrate, sodium potassium sodium tartrate and sodium gluconate; the buffer is selected from at least one of sodium borate, sodium acetate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate and triethanolamine.

[0061] An anodizing method comprises the following steps:

[0062] (1) pre-treating the metal sheet; the pre-treatment includes grinding, polishing and degreasing, each of which also includes water washing;

[0063] (2) contacting the metal sheet with the aforementioned anodizing solution for direct current anodizing; wherein the anodizing voltage is 20-40 V, the anodizing temperature is 20-40° C., and the anodizing time is 20-60 min;

[0064] (3) Sealing the treated plate obtained by anodization; the sealing process comprises: placing the treated plate in a nickel acetate solution for sealing for 20-60 minutes, and then drying at 60-80° C. for 10-30 minutes.

[0065] An oxidized plate obtained by the above-mentioned anodizing method, the oxidized plate comprising a magnesium-aluminum composite plate and an anodic oxide film covering both surfaces of the magnesium-aluminum composite plate;

[0066] The thickness of the anodized film layer on the magnesium surface of the magnesium-aluminum composite plate is 1-8 μm;

[0067] The thickness of the anodized film layer on the aluminum surface of the magnesium-aluminum composite plate is 1-7 μm.

[0068] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.

[0069] Example 1

[0070] (1) Pretreatment: grinding, polishing, degreasing, etc. of the magnesium-aluminum composite plate.

[0071] (2) Anodizing: Using water as solvent, an anodic oxidation solution (pH=10) was prepared according to the following formula: 0.2 g / L potassium hydroxide, 30 g / L potassium carbonate, 20 g / L sodium tungstate, 5 g / L sodium tartrate, and 20 g / L sodium phosphate. The pre-treated magnesium-aluminum composite sheet was placed in the prepared anodic oxidation solution and pulse anodized at 40 V and 40 ° C for 60 min.

[0072] (3) Sealing: The treated plate obtained by anodization is placed in a nickel acetate solution for sealing for 20 minutes, and then dried at 60° C. for 30 minutes.

[0073] Example 2

[0074] (1) Pretreatment: grinding, polishing, degreasing, etc. of the magnesium-aluminum composite plate.

[0075] (2) Anodizing: Using water as solvent, an anodic oxidation solution (pH=13) was prepared according to the following formula: 2 g / L ammonia water, 120 g / L ammonium bicarbonate, 5 g / L sodium molybdate, 20 g / L sodium citrate, and 5 g / L sodium borate. The pre-treated magnesium-aluminum composite sheet was placed in the prepared anodic oxidation solution and subjected to AC anodizing at 20 V and 20° C. for 40 min.

[0076] (3) Sealing: The treated plate obtained by anodization is placed in a nickel acetate solution for sealing for 60 minutes, and then dried at 80° C. for 10 minutes.

[0077] Example 3

[0078] (1) Pretreatment: grinding, polishing, degreasing, etc. of the magnesium-aluminum composite plate.

[0079] (2) Anodizing: Using water as solvent, an anodic oxidation solution (pH=12) was prepared according to the following formula: 1 g / L sodium hydroxide, 60 g / L potassium carbonate, 10 g / L sodium molybdate, 10 g / L disodium ethylenediaminetetraacetic acid, and 5 g / L triethanolamine. The pre-treated magnesium-aluminum composite sheet was placed in the prepared anodic oxidation solution and subjected to direct current anodizing at 30 V and 30° C. for 20 min.

[0080] (3) Sealing: The treated plate obtained by anodization is placed in a nickel acetate solution for sealing for 30 minutes, and then dried at 70° C. for 20 minutes.

[0081] Example 4

[0082] (1) Pretreatment: grinding, polishing, degreasing, etc. of the magnesium-aluminum composite plate.

[0083] (2) Anodizing: Using water as solvent, an anodic oxidation solution (pH=11) was prepared according to the following formula: 0.1 g / L sodium hydroxide, 150 g / L potassium bicarbonate, 3 g / L magnesium tungstate, 30 g / L sodium gluconate, and 30 g / L sodium acetate. The pre-treated magnesium-aluminum composite sheet was placed in the prepared anodic oxidation solution and pulse anodized for 120 min at 10 V and 60 ° C.

[0084] (3) Sealing: The treated plate obtained by anodization is placed in a nickel acetate solution for sealing for 40 minutes, and then dried at 75° C. for 15 minutes.

[0085] Example 5

[0086] (1) Pretreatment: grinding, polishing, degreasing, etc. of the magnesium-aluminum composite plate.

[0087] (2) Anodizing: Using water as solvent, an anodic oxidation solution (pH=9) was prepared according to the following formula: 3 g / L potassium hydroxide, 20 g / L sodium bicarbonate, 30 g / L ammonium molybdate, 3 g / L potassium sodium tartrate, and 3 g / L disodium hydrogen phosphate. The pre-treated magnesium-aluminum composite sheet was placed in the prepared anodic oxidation solution and subjected to direct current anodizing at 100 V and 15° C. for 10 min.

[0088] (3) Sealing: The treated plate obtained by anodization is placed in a nickel acetate solution for sealing for 50 minutes, and then dried at 65° C. for 20 minutes.

[0089] Example 6

[0090] (1) Pretreatment: grinding, polishing, degreasing, etc. of the magnesium-aluminum composite plate.

[0091] (2) Anodizing: Using water as solvent, an anodic oxidation solution (pH=10) was prepared according to the following formula: 0.2 g / L ammonia water, 20 g / L sodium carbonate, 3 g / L ammonium tungstate, 3 g / L sodium oxalate, and 3 g / L sodium dihydrogen phosphate. The pre-treated magnesium-aluminum composite sheet was placed in the prepared anodic oxidation solution and subjected to AC anodizing at 10 V and 15° C. for 10 min.

[0092] (3) Sealing: The treated plate obtained by anodization is placed in a nickel acetate solution for sealing for 20 minutes, and then dried at 60° C. for 10 minutes.

[0093] Comparative Example 1

[0094] The magnesium-aluminum composite plate was treated according to the method of Example 3, except that sodium molybdate was not added.

[0095] Comparative Example 2

[0096] The magnesium-aluminum composite plate was treated according to the method of Example 3, except that disodium ethylenediaminetetraacetic acid was not added.

[0097] Comparative Example 3

[0098] The magnesium-aluminum composite plate is treated according to the method of Example 3, except that sodium molybdate and disodium ethylenediaminetetraacetate are not added.

[0099] Comparative Example 4

[0100] The preferred anodizing solution described in CN1997777A was used for oxidation, and the conditions were: Na2HPO4 92.2 g / L, KOH 31 g / L, amino-methyl propanol 15.5 g / L, 97 0.20g / L, pH:11.2, voltage 200V, temperature 25℃, time 10min.

[0101] Comparative Example 5

[0102] The preferred anodizing solution described in CN110629267A was used for oxidation, and the conditions were: 50 g / L sodium carbonate, 10 g / L sodium borate, 100 g / L glycerol, 30 g / L sodium tartrate, pH: 10.4, voltage 80 V, temperature 80° C., and time 90 min.

[0103] Test Example 1 Characterization of Microstructure

[0104] The samples prepared in Example 3 were observed by scanning electron microscope. Figure 1 This is the SEM image of the aluminum surface. The morphology is similar to that of ordinary aluminum anodized film, which is porous. Figure 2 This is the SEM image of the magnesium surface, which has a dry riverbed-like morphology and contains microcracks.

[0105] Test Example 2: Appearance and film thickness test

[0106] Appearance and film thickness tests were performed on Examples 1-5 and Comparative Examples 1-5. The test results are shown in Table 1.

[0107] 1. Appearance inspection: Visually observe whether the sample surface has any appearance defects such as powdering;

[0108] 2. Film thickness test: The thickness of the anodized film on both sides of the sample was tested using a coating thickness meter. The model of the testing instrument used was PHYNIX Pocket-Surfix FN2.2.

[0109] Table 1

[0110]

[0111]

[0112] It can be seen from the results in Table 1 that the anodized films prepared in Examples 1-6 of the present invention have good appearance, are uniform and complete, and the thickness of the oxide films on both sides can reach up to 8 μm and 7 μm.

[0113] Under the same operating conditions as Example 3, Comparative Example 1 did not add sodium molybdate, and the film thickness decreased, Comparative Example 2 did not add disodium ethylenediaminetetraacetate, and the uniformity of the film layer decreased, and Comparative Example 3 did not add sodium molybdate and disodium ethylenediaminetetraacetate, and the film thickness and film uniformity both decreased. Therefore, it can be explained that the molybdate and / or tungstate and the complexing agent in the present invention have a synergistic effect, which is beneficial to the thickening of the film layer and the improvement of the uniformity of film formation, and can ensure that both sides of the magnesium-aluminum composite plate grow uniformly and stably in the oxidation solution, thereby forming a complete and uniform anodized film layer.

[0114] The oxidation voltage in Comparative Example 4 was too high, causing both sides of the plate to be powdered; the oxidation temperature in Comparative Example 5 was relatively high, causing the aluminum surface to be powdered.

[0115] Test Example 3 Neutral Salt Spray Test

[0116] Test method:

[0117] 1. NaCl concentration: 5%, spray liquid pH: 6.5-7.2, test temperature: 35℃±1℃, spray pressure: 0.07-0.17MPa, spray method: continuous spray, spray volume: 1.5±0.5ml / hr (funnel area 80cm 2 ).

[0118] 2. Sample placement method: Place the sample face up, remove it from the test chamber after 48 hours, and check the appearance of the sample; then rinse it gently with warm water not higher than 38°C, wipe it clean with a dust-free cloth, and check the appearance of the sample after placing it at room temperature for 2 hours.

[0119] The test results of Examples 1-6 of the present invention are: no corrosion or discoloration on the surface; the test results of Comparative Examples 1-3 are: slight discoloration on the surface; the test result of Comparative Example 4 is: both the Al surface and the Mg surface are corroded; the test result of Comparative Example 5 is: the Al surface is corroded, and the Mg surface is not corroded.

[0120] The above test results indicate that the anodized film prepared in the present application has better salt spray resistance than the comparative example.

[0121] Test Example 4 Adhesion Test

[0122] Test method:

[0123] Use a cutting tool or a single-edged tool to draw 10×10 (100) 1mm×1mm small grids. Each line should be deep enough to reach the substrate. Use a brush or dust-free cloth to clean the debris in the test area. Cut about 55mm long 3M610 tape, and use your fingernails to flatten the area above the grid area to ensure that the tape is in good contact with the film layer. The tape length should be at least 20mm longer than the grid. Stick the tape on and let it stand for (90±30)s. Hold one end of the tape in the air and quickly tear off the tape within 1s at an angle as close to 60° as possible in the vertical direction. Test the same position once, check the film shedding condition, and make a judgment based on the qualified criterion (adhesion reaches or exceeds 4B for qualified).

[0124] The test results of Examples 1-6 of the present invention are: the adhesion on both sides is 4B; the test results of Comparative Examples 1-3 are: the adhesion on the Al surface is 3B, and the adhesion on the Mg surface is 3B; the test result of Comparative Example 4 is: the adhesion on the Al surface is 1B, and the adhesion on the Mg surface is 2B; the test result of Comparative Example 5 is: the adhesion on the Al surface is 1B, and the adhesion on the Mg surface is 4B.

[0125] The above test results indicate that the anodized film prepared in the present application has better adhesion performance than the comparative example.

[0126] Test Example 5: Boiling Test

[0127] Test method:

[0128] Immerse the test sample completely in pure water at 80℃±2℃, boil it for 30 minutes, take it out, let it stand at room temperature for 2 hours, check whether there is any abnormality on the surface of the sample film layer, and conduct an adhesion test.

[0129] The test results of Examples 1-6 of the present invention are: no corrosion or discoloration on the surface, and the adhesion on both sides is 4B; the test results of Comparative Examples 1-3 are: slight discoloration on the surface, and the adhesion on both sides is 3B; the test results of Comparative Example 4 are: Al surface discoloration, adhesion is 1B, Mg surface corrosion and discoloration, and adhesion is 2B; the test results of Comparative Example 5 are: Al surface discoloration, adhesion is 1B, Mg surface has no corrosion or discoloration, and adhesion is 4B.

[0130] The above test results indicate that the anodized film prepared in the present application has better water boiling resistance than the comparative example.

[0131] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An anodic oxidation solution, characterized in that: The anodizing solution comprises the following components: alkali, alkaline salt, molybdate and / or tungstate, complexing agent, buffer and water; The mass ratio of the molybdate and / or tungstate to the complexing agent is 1:0.25-4; The base is hydroxide and / or ammonia; The alkaline salt is a carbonate and / or a bicarbonate; The molybdate is selected from at least one of sodium molybdate, magnesium molybdate, ammonium molybdate and lithium molybdate; The tungstate is selected from at least one of sodium tungstate, magnesium tungstate, ammonium tungstate and lithium tungstate; The complexing agent is selected from at least one of sodium oxalate, sodium citrate, disodium edetate, sodium tartrate, sodium potassium tartrate and sodium gluconate; The buffer is selected from at least one of sodium borate, sodium acetate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate and triethanolamine.

2. The anodizing solution according to claim 1, wherein The pH value of the anodizing liquid is greater than 7.

3. The anodizing solution according to claim 2, wherein: The pH value of the anodizing liquid is 10-13.

4. The anodizing solution according to claim 1 or 2, wherein: The molybdate and / or tungstate is the same as the cation of the complexing agent.

5. The anodizing solution according to claim 1 or 2, wherein: The hydroxide is sodium hydroxide and / or potassium hydroxide.

6. The anodizing solution according to claim 1 or 2, wherein: The content of the alkali is 0.1-3 g / L.

7. The anodizing solution according to claim 6, wherein: The content of the alkali is 0.2-2 g / L.

8. The anodizing solution according to claim 1, wherein: The alkaline salt is selected from at least one of sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate, potassium bicarbonate and ammonium bicarbonate.

9. The anodizing solution according to claim 8, wherein: The alkaline salt is sodium carbonate and / or potassium carbonate.

10. The anodizing solution according to claim 1, wherein: The content of the alkaline salt is 20-150 g / L.

11. The anodizing solution according to claim 10, wherein: The content of the alkaline salt is 30-120 g / L.

12. The anodizing solution according to claim 1, wherein The content of the molybdate and / or tungstate is 3-30 g / L.

13. The anodizing solution according to claim 12, wherein: The content of the molybdate and / or tungstate is 5-20 g / L.

14. The anodizing solution according to claim 1, wherein: The complexing agent is selected from at least one of disodium ethylenediaminetetraacetate, sodium tartrate and sodium potassium tartrate.

15. The anodizing solution according to claim 1, wherein: The content of the complexing agent is 3-30 g / L.

16. The anodizing solution according to claim 15, wherein: The content of the complexing agent is 5-20 g / L.

17. The anodizing solution according to claim 1, wherein: The buffer is sodium phosphate and / or triethanolamine.

18. The anodizing solution according to claim 1, wherein: The content of the buffer is 3-30 g / L.

19. The anodizing solution according to claim 18, wherein: The content of the buffer is 5-20 g / L.

20. An anodizing method, characterized in that: The metal sheet is brought into contact with the anodizing liquid according to any one of claims 1 to 19 for anodizing.

21. The anodizing method according to claim 20, wherein: The anodizing method is selected from one of direct current anodizing, alternating current anodizing and pulse anodizing.

22. The anodizing method according to claim 21, wherein: The anodizing method is direct current anodizing.

23. The anodizing method according to claim 21, wherein: The anodizing voltage is 10-100V, the anodizing temperature is 15-60°C, and the anodizing time is 10-120min.

24. The anodizing method according to claim 23, wherein: The anodizing voltage is 20-40V, the anodizing temperature is 20-40°C, and the anodizing time is 20-60min.

25. The anodizing method according to claim 20 or 21, wherein: The method further comprises: performing a pre-treatment on the metal sheet before the anodizing.

26. The anodizing method according to claim 25, wherein: The pre-treatment includes grinding, polishing and degreasing, wherein each step also includes water washing.

27. The anodizing method according to claim 20 or 21, wherein: The method further comprises: sealing the pores of the treated plate obtained by anodization.

28. The anodizing method according to claim 27, wherein: The sealing process includes: placing the treated plate into a nickel acetate solution for sealing for 20-60 minutes, and then drying at 60-80° C. for 10-30 minutes.

29. An oxidized plate obtained by the anodizing method according to any one of claims 20 to 28.

30. The oxidation plate according to claim 29, wherein The oxidation plate comprises a metal plate and an anodic oxidation film covering at least one side of the metal plate.

31. The oxidation plate according to claim 30, wherein The metal plate is a magnesium-aluminum composite plate.

32. The oxidized plate according to claim 31, wherein The thickness of the anodized film layer on the magnesium surface of the magnesium-aluminum composite plate is 1-8 μm.

33. The oxidized plate according to claim 31, wherein The thickness of the anodized film layer on the aluminum surface of the magnesium-aluminum composite plate is 1-7 μm.

Citation Information

Patent Citations

  • Titanium alloy anodic oxidation alkaline electrolyte and preparation technique of color film layer

    CN103320840A

  • Alkaline anodizing liquid and method for aluminum products

    CN110629267A

  • Method of anodizing metallic surfaces and compositions

    CN1997777A

  • Magnesium alloy anodizing electrolyte and method for preparing anodic oxide film by electrolyte

    CN105063721A